2018
DOI: 10.1007/s10840-018-0342-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving sudden cardiac death risk stratification by evaluating electrocardiographic measures of global electrical heterogeneity and clinical outcomes among patients with implantable cardioverter-defibrillators: rationale and design for a retrospective, multicenter, cohort study

Abstract: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03210883.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our study confirmed that after multivariable adjustment in competing risk analysis, there is an independent association between SVG direction and sustained ventricular tachyarrhythmias leading to appropriate ICD therapies, but not competing death outcome. The SVG vector points towards the area of the myocardium with the shortest excited state, 4, 9 and deviations from normal suggest the accumulation of a critical mass of abnormal electrical substrate, which might predispose to ventricular arrhythmias. Our results support the use of GEH, and specifically the orientation of the area SVG vector, as a marker of abnormal underlying electrophysiological substrate responsible for a propensity for sustained ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study confirmed that after multivariable adjustment in competing risk analysis, there is an independent association between SVG direction and sustained ventricular tachyarrhythmias leading to appropriate ICD therapies, but not competing death outcome. The SVG vector points towards the area of the myocardium with the shortest excited state, 4, 9 and deviations from normal suggest the accumulation of a critical mass of abnormal electrical substrate, which might predispose to ventricular arrhythmias. Our results support the use of GEH, and specifically the orientation of the area SVG vector, as a marker of abnormal underlying electrophysiological substrate responsible for a propensity for sustained ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and protocol has been previously described. 9 In brief, we conducted a retrospective, multicenter cohort study that included data from six academic medical centers in the United States: OHSU in Portland, OR, Veteran Administration Portland Healthcare System (Portland VA) in Portland, OR, Beth Israel Deaconess Medical Center (BIDMC) in Boston, MA, the University of Colorado (U Colorado) in Aurora, CO, Cedars-Sinai Medical Center (CSMC) in Los Angeles, CA, and Stanford University (Stanford U) in Palo Alto, CA. We included all patients above the age of 18 years with chronic systolic heart failure (HF) due to infarct-related cardiomyopathy and/or NICM, who underwent implantation of any ICD [including single chamber, dual-chamber, cardiac resynchronization defibrillator (CRT-D), or subcutaneous] for primary prevention of SCD between the years of 1996 and 2019, and had an available digital 12-lead ECG recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed data from the retrospective, multicenter cohort study "Global Electrical Heterogeneity and Clinical Outcomes" (GEHCO). [13,14] The study was approved by the Institutional Review Boards at the Oregon Health & Science University and each participating institution. The study collected digital 12-lead ECG signal recorded before implantation of implantable cardioverter-defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D).…”
Section: Study Populationmentioning
confidence: 99%
“…Vectorcardiographic (VCG) global electrical heterogeneity (GEH) characterizes spatial dispersion in total recovery time 12 , 13 across ventricles that can be due to dispersion in either ventricular activation or refractoriness. 14 In the multicentre retrospective cohort study of primary prevention ICD recipients Global Electrical Heterogeneity and Clinical Outcomes (GEHCO) study, 15 , 16 competing risks analysis showed differences in GEH phenotype between patients who developed sustained VT/VF and appropriate ICD therapies as compared to those who died without ventricular arrhythmia. Furthermore, different GEH phenotypes comprised short-term (triggers or transient substrates of SCD) vs. long-term (persistent SCD substrates) predictor profiles.…”
Section: Introductionmentioning
confidence: 99%